Estratégias gerenciais e o fluxo de valor: estudo no sistema público de ensino a distância - Ricardo Jorge da Cunha Costa Nogueira (2014)
The purpose of this thesis was to map the future value stream - VSM for the tutorial process of the National Public Administration of Amazon - PNAP/AM, from different perceptions (coordinators, tutors and students) by identifying the representations of strategies for persistence in the flow of value through best practices and possible adjustments in the process, in order to reduce student dropout rates. This required: identify from a multidimensional view of the different perceptions that management strategies implemented in the mentoring process are correlated with motivation and persistence in mitigating ongoing academic evasion; raise the profile of distance tutors the PNAP/AM and managerial characteristics that generate effective contribution to students' motivation and persistence; analyze how the Public Institutions of Higher Education - IPES, different regional centers of distance education in Brazil dealing with the limitations and develop their managerial strategies with the mentoring process and map the current state and propose a desirable future state, by way of flow value - VSM to the mentoring model applied to the correction activities PNAP/AM process. About the methodology used is emphasized that the unit of observation was limited to the Undergraduate course PNAP Administration and the unit of analysis was formed by students of the Bachelor of Public Administration PNAP the Federal University of Amazon - UFAM; tutors of the Bachelor of Public Administration PNAP UFAM; Course coordinators and the PNAP different regional centers of distance education in Brazil. We sought in the literature review, theoretical support and tools, being one of the possibilities found the adaptation of Lean Office by way of VSM applied to the value stream of the tutorial process chain, thus portraying the "current state" and projecting a "future state" desirable, harmonized with the local reality. About the results achieved in research with students, found that, of those who like and agree with the strategy used by the tutor to retain the attention of the class and pursue student motivation for learning, assessment of variable activities is the most important with 80.2% contribution of the factor model, followed by participation in forums with 77.7% of the factor loading contribution. Have the research coordinators was found that, among the possible strategies developed by the mentoring process, aiming at reducing dropout rates are: the need for systematic contact for redemption of the student, with 25% and focus on training of tutors 25%. Other strategies such as regular meetings with tutors, collection of tasks, quick responses to the student, and others appear, however, welldispersed form. Regarding the findings, it can be inferred that in this research, the VSM tool only indicates the points of improvements, from there the actions depend on each actor. The thesis presented important findings regarding the claims made by the tutoring PNAP/AM and treat itself to an experimental mapping, there still aspects that require further improvement.